2010
DOI: 10.1007/s11060-010-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CypA inhibits interleukin-8 (IL-8) and IL-8-mediated proliferation and tumor growth of glioblastoma cells through down-regulated NF-κB

Abstract: Although cyclophilin A (CypA) has been reported to be over-expressed in cancer cells and solid tumors, its expression and role in glioblastomas have not been studied. Herein, we show that expression of CypA in human glioblastoma cell lines and tissues is significantly higher than in normal human astrocytes and normal counterparts of brain tissue. To determine the role of over-expressed CypA in glioblastoma, stable RNA interference (RNAi)-mediated knockdown of CypA (CypA KD) was performed in gliobastoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…However, the functional role of the closely related PPIase family member CypA (PPIA) in skeletal development remains elusive. In previous reports, we demonstrated a close relationship between CypA and NF-B signaling (22,28). NF-B was found to regulate certain aspects of endochondral ossification during embryogenesis (29,30).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, the functional role of the closely related PPIase family member CypA (PPIA) in skeletal development remains elusive. In previous reports, we demonstrated a close relationship between CypA and NF-B signaling (22,28). NF-B was found to regulate certain aspects of endochondral ossification during embryogenesis (29,30).…”
Section: Discussionmentioning
confidence: 68%
“…We had previously demonstrated that CypA knockdown (Kd) results in the downregulation of NF-B/p65 (RelA, a subunit of NF-B) in glioblastoma cell lines and a murine myoblast line, C2C12 (22,28). Decreased NF-B/p65 expression levels were also observed in CypA Kd mouse chondrogenic ATDC5 stable clones, 2T7 and 2T3, as well as in CypA KO mouse proximal tibia growth plates ( Fig.…”
Section: Effect Of Cypa Deficiency On Chondrocyte Differentiation In mentioning
confidence: 89%
“…For example, the stability, localisation and activity of the p65 subunit of NF-κB was recently shown to be regulated by association with CypA because its downregulation impaired production of NF-κB-induced cytokines while reducing the proliferation of glioblastoma cells. 32,33 Similar to CypA, genetic ablation of CypB reduces glioma cell survival and proliferation, as shown both in vitro and in vivo. 34,35 We found that multiple cyclophilins -CypA, CypB and CypH -directly interact with a newly identified target, p38MAPK, facilitating isomerisation of Pro224, which in turn is required to regulate phosphorylation of kinase regulatory Thr-Gly-Tyr motif.…”
Section: Discussionmentioning
confidence: 94%
“…S4A), and so was used for the calculation of a radial distribution function. At this point, cells have had time to migrate (18) and are adherent. One might ask why the cells would migrate in the bulk culture, whereas they are not observed to move on the SCBC platform.…”
Section: Predicting Spatial Distributions Of Gbm Cells From the Measuredmentioning
confidence: 99%